Risk Management Tools and Financial Performance of Commercial Banks in Rwanda: A Case Study of Banque Populaire Du Rwanda Public Limited Company - Bahati, Aimable (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2021)
The study is about risks management tools on financial performance of commercial banks in Rwanda, the case study of BPR Plc. The general objective of this research was to assess the contribution of risks management tools on financial performance of commercial banks in Rwanda, taking a case study of BPR. Specific objectives includes to ascertain risks management tools used by BPR in managing its asset; to analyze the financial performance of BPR in Rwanda since 2015 to 2018 and to find the link amid risks management tools and financial performance of commercial banks in Rwanda. The results of this research are useful for academic purpose as reference, to institutions, which will access the findings to address risk issues and improve their control measures against risk. The main theory applied in this research is Agency theory. This research adopted descriptive and correlation research designs and is both qualitative and quantitative research. Forty-two (42) is target population used; census was applied in this research as the sampling technique since the target population is small and data were analyzed using SPSS version 20 to generate frequency tables, charts, and regression analysis. The research revealed that at BPR Plc, use of risk management tools has a great positive relationship with the financial performance of BPR as it is being indicated by the respondents about standard and reports, position limit and rules, investment guideline and strategies whether help in financial performance in BPR, many respondents were in agreement with this statement as it is indicated by a high means and homogeneity in responses as the standard deviations obtained for all items of independent variables were less than one (SD<1). for objective two, it was seen that BPR Plc financial performance increased considerably since 2015 to 2018 as results of risk management tools; for relationship, the results found that risk management tools greatly influence BPR financial performance as justified by P-values which are positive and statistically significant respectively for position limit and rules (p=0.003), standard and reports (p=0.034), investment guideline and strategies (p=0.023) which are less than the significance level (P<0.05) from multiple regression analysis. The conclusion is that risk management tools greatly influence banks financial performance. So far, much is already done by the Bank to overcome and mitigate risk in all BPR operations but there is need to emphasize on new strategies to improve on standards, rules and regulation to enforce risk mitigation. In today’s BPR daily business; technology is increasing, process and procedures are tightened, account manipulation are restricted. This has greatly reduced reputation and financial risk leading to increase in financial performance. The further studies should be carried out on implementation of risk management strategies and financial performance in banking industry.